Preventing intrusive memories after trauma via a brief intervention involving Tetris computer game play in the emergency department: a proof-of-concept randomized controlled trial - Iyadurai, L; Blackwell, S; Meiser-Stedman, R; Watson, P; Bonsall, M; Geddes, J; De Ozorio Nobre, A; Holmes, E (Springer Nature, 2017)
After psychological trauma, recurrent intrusive visual memories may be distressing and disruptive. Preventive interventions post-trauma are lacking. Here we test a behavioural intervention after real-life trauma derived from cognitive neuroscience. We hypothesised that intrusive memories would be significantly reduced in frequency by an intervention involving a computer game with high visuospatial demands (Tetris), via disrupting consolidation of sensory elements of trauma memory. The Tetris-based intervention (trauma memory reminder cue plus c. 20 minute game play) versus attention-placebo control (written activity log - standardised task for same duration) were both delivered in an Emergency Department within 6 hours of a motor-vehicle accident, in a randomized controlled trial assessing intrusive memory frequency in the subsequent week. Results vindicated the efficacy of the Tetris-based intervention compared to the control condition: there were fewer intrusive memories overall (primary outcome), and time-series analyses showed intrusion incidence declined more quickly. There were convergent findings on a measure of clinical post-trauma intrusion symptoms at one week, but not on other symptom clusters or at 1 month. Results of this proof-of-concept study suggest that a larger trial, powered to detect differences at one month, is warranted. Participants found the intervention easy, helpful and minimally distressing. By translating emerging neuroscientific insights and experimental research into the real world, we offer a promising new low-intensity psychiatric intervention that could prevent debilitating intrusive memories following trauma.